Advances in halide ion-mediated advanced oxidation processes for high-salinity wastewater treatment: Mechanisms of reactive oxidative species transformation and halogenated by-product formation - Yu Wang; Bing Yang; Yumin Zhang; Lingli Li; Chao Zhu; Yurui Li; Shaoqing Chen; Lili Ma; Mingyan Chen; Yucheng Liu (Chemical Engineering Journal, 2026)

Deep seismic sounding methods for imaging the fine structure of the Earth’s crust - Yurui Guan; Tao Xu; Zhiming Bai; Jiyan Lin; Dengda Zhu; Jiwen Teng (Science China Earth Sciences, 2026)

Subchronic exposure of tire wear particles leachate induces oxidative stress and DNA damage in zebrafish (Danio rerio) brain - Bo Cheng; Yurui Hou; Yuqing Hou; Lanjun Wang; Yibo Gao; Yuhan Ye; Tao Tang; Baihui Shi; Junpu Wang; Lusheng Zhu; Jun Wang; Young Mo Kim; et al. (Journal of Environmental Management, 2026)

The global APSES transcription factor PeStuA modulates growth, development, stress response, hydrophobicity, patulin biosynthesis and pathogenicity in Penicillium expansum - Yanling Wang; Yurui Wu; Qianrun Liang; Xin Chen; Jinfen Zhu; Wei Li (International Journal of Food Microbiology, 2026)

Decolorization of Antarctic krill hydrolysate for salt reduction in surimi gel: improvement of taste, gel properties, and flavor profile - Yurui Zhang; Bo Wang; Yan Li; Xin Jiang; Shangkun Li; Keqiang Lai; Guoping Zhu; Wenzheng Shi (Food Research International, 2026)

Flood risk assessment of urban rail transit stations based on uncertainty analysis - Liang Mu; Zixu Yan; Yurui Kang; Guangyu Zhu (Stochastic Environmental Research and Risk Assessment, 2025)

Oxidizing agents alter surface reaction pathways in heterogeneous Fenton reactions: Surface electron transfer interactions and altered bond breaking processes in contaminants - Yurui Li; Haoran Wu; Bing Yang; Chao Zhu; Shijie Zhou; Lili Ma; Lingli Li; Mingyan Chen; Heng Guo; Yucheng Liu (Journal of Environmental Chemical Engineering, 2025)

Paris saponin VII restrains PD-L1 mediated immune evasion through the AKT1 and STAT3 signaling pathways - Yudi Wang; Yanli Li; Yurui Zhang; Yitong Li; Leilei Zhao; Lanxin Tong; Xiao Zhu; Jianyong Wang; Yucui Dong (Chemico-Biological Interactions, 2025)

Design of the TP-1B satellite’s laser retro-reflector array and analysis of laser ranging - Qingshan Luo; Xu Liu; Tao Yang; Yurui Xu; Wei Zhu; Yunsheng Yao (Advances in Space Research, 2025)

Effect of CFEM proteins on pathogenicity, patulin accumulation and host immunity of postharvest apple pathogens Penicillium expansum - Yanling Wang; Jie Gao; Xin Chen; Yanqi Huang; Yurui Wu; Jinfen Zhu; Wei Li (International Journal of Food Microbiology, 2025)

GepA, a GGDEF-EAL protein, regulates biofilm formation and swimming motility in Vibrio parahaemolyticus - Miaomiao Zhang; Yurui Zhu; Xue Li; Xi Luo; Hui Sun; Shuhui Xiong; Renfei Lu; Yiquan Zhang (Archives of Microbiology, 2025)

The clinical characteristics of Streptococcus equi ssp. zooepidemicus causing acute death in pigs and its prevention with chimeric monoclonal antibodies - Chen Yuan; Yuchang Wang; Xiaowen Zhang; Xingyu Tian; Ying Liang; Fei Pan; Haoshuai Song; Linya Xia; Zhihui Wu; Wenqing Wang; Xiaowen Zhang; Yurui Xie; et al. (Veterinary Microbiology, 2025)

Multidimensional deconstruction and workable solutions for addressing China's food security issues: From the perspective of sustainable diets - Xiaohua Zhu; Yan Zhang; Yuanyuan Zhu; Yurui Li; Jiaxing Cui; Bohua Yu (Land Use Policy, 2025)

Effects of light intensity and light duration on growth performance and ovarian development in red swamp crayfish Procambarus clarkii (Girard, 1852) - Long Wang; Meng Hu; Lin Cai; Yurui Wang; Tianyu Guan; Chuankun Zhu; Hui Wang; Guiling Wang; Jiale Li (Aquaculture International, 2025)

Experimental study on environmental chemical effect and purification treatment of waste slurry in horizontal directional drilling - Pinghe Sun; YuRui He; Shengwei Zhou; Habiyakare Erneste; Qiang Gao; Zihao Zou; Junyi Zhu (Tunnelling and Underground Space Technology, 2024)

The shift to plant-based dietary patterns in China would have significant effects on cultivated land resources - Xiaohua Zhu; Yan Zhang; Yuanyuan Zhu; Yurui Li (Science Bulletin, 2024)

Effects of chronic abamectin stress on growth performance, digestive capacity, and defense systems in red swamp crayfish (Procambarus clarkii) - Tianyu Guan; Long Wang; Meng Hu; Qianqian Zhu; Lin Cai; Yurui Wang; Peng Xie; Jianbin Feng; Hui Wang; Jiale Li (Aquatic Toxicology, 2024)

Pruning and quantization algorithm with applications in memristor-based convolutional neural network - Mei Guo; Yurui Sun; Yongliang Zhu; Mingqiao Han; Gang Dou; Shiping Wen (Cognitive Neurodynamics, 2024)

Cloning and Expression of Sox2 and Sox9 in Embryonic and Gonadal Development of Lutraria sieboldii - Min Lu; Zenghou Xing; Yurui Zhou; Youhou Xu; Huijing Peng; Jie Zou; Solomon Felix Dan; Zhicai She; Pengliang Wang; Jinfeng Liu; Shaomin Qin; Jialin Yang; et al. (Fishes, 2022)
The Sox family plays essential roles as transcription factors in vertebrates; however, little is known about the Sox family in Lutraria sieboldii. L. sieboldii are pleasant to eat with a short growth cycle and have become one of the best bottom-seeded enrichment species in Guang Xi. In this study, Sox2 (named LsSox2) and Sox9 (named LsSox9) from L. sieboldii were cloned, and their expression patterns were analyzed. The length of the LsSox2 gene coding sequence was 1011 bp, encoding 336 amino acids, and LsSox9 was 1449 bp, encoding 482 amino acids. LsSox2 had its highest expression levels in the ovary, which were 356 times those in testis, whereas LsSox9 presented higher expression in testis, which was 6 times more highly expressed than in the ovary. LsSox2 exhibited the highest expression during the morula stage, which was 20 times that of the D-shaped larvae or zygote. LsSox9 exhibited two expression peaks, one at the four-cell stage and the other at the trochophore stage, while the lowest expression was in the zygote. LsSox9 was 73 times more highly expressed in the four-cell stage than in the zygote stage. During gonadal development, LsSox2 presented the highest expression in the mature ovary, which was 756 times more highly expressed than in mature testis. LsSox9 presented higher expression in testis at the emission stage which was 6 times more highly expressed than in the ovary. These results indicate that LsSox2 and LsSox9 may play important roles in embryonic and gonadal development.

Characterization of the cellulolytic bacteria communities along the gastrointestinal tract of Chinese Mongolian sheep by using PCR-DGGE and real-time PCR analysis - Yan Zeng; Dong Zeng; Yan Zhang; Xueqin Ni; Yurui Tang; Hui Zhu; Hesong Wang; Zhongqiong Yin; Kangcheng Pan; Bo Jing (World Journal of Microbiology and Biotechnology, 2015)

Characteristics of porosity and permeability layer of fossil Halimeda reef mineral rock of Miocene in the Xisha Islands and its genetic model - Hong Xu; Yurui Zhu; G. P. Eberli; Wei Luo; Xinwei Zhao; Ying Cai; Xinyu Liu; Guijing Yan; Bolin Zhang; Kai Wei; Ruyong Cui (Acta Oceanologica Sinica, 2015)

Biogenic carbonate formation and sedimentation in the Xisha Islands: evidences from living Halimeda - Hong Xu; Xinwei Zhao; G. P. Eberli; Xinyu Liu; Yurui Zhu; Ying Cai; Wei Luo; Guijing Yan; Bolin Zhang; Kai Wei; Jian Shi (Acta Oceanologica Sinica, 2015)

Bioherm petroleum reservoir types and features in main sedimentary basins of the South China Sea - Hong Xu; Jing Sun; Jing Liao; Gang Dong; Jinqing Liu; Hongying Song; Zhenfeng Wang; Zhipeng Sun; Qinghuan Jin; Li Zhang; Kai Wei; Yurui Zhu; et al. (Journal of Earth Science, 2012)